Celebratory reflections, appreciations, clarifications, and comments. (August 2017) - Fetterman, David; Wandersman, Abraham
Highlights: The search for credible and actionable evidence to improve is a global phenomenon. Empowerment evaluation is part this phenomenon. Michael compliments our use of the critical friend to help us improve our work and the community's complex initiatives, and who we are as evaluators. Michael Patton commented about empowerment evaluation being "exemplary" in its "openness to dialogue and reflective practice". Michael captured empowerment evaluation's commitment to process use. We appreciate Alkin's recommendation to focus on prescriptive theory. There is nothing as practical as a good theory (Lewin, 1952; Weiss, 1995). We thank each and every one of our colleagues for their contributions today and over the last 21 years.